The Effect of Leadership Behavior on Managerial Creativity of Saline Water Conversion Corporation Employees: Applied Study on Shuqaiq Desalination Plants Employees - Etwadi, Yahya Ibrahim (Journal of Economic, Administrative and Legal Sciences, 2020)
The study aimed to identify the data of some variables of leadership behavior, and to identify the reality of managerial creativity of employees and administrators in the Saline Water Conversion Corporation. Also, to identify the data of some personal and functional variables of workers at the level of their managerial creativity. To achieve the study’s aims, the researcher followed the descriptive approach. The study was applied to a sample consisted of 100 employees of the Saline Water Conversion Corporation, using a questionnaire distributed to them. The study came with some conclusions, most important of with are: 1) The level of managerial creativity of the Saline Water Conversion Corporation employees was high. 2) The analysis and connectivity were the least available elements of managerial innovation. 3) The elements of managerial creativity can be arranged according to their availability as: (flexibility, originality, sensitivity to problems, intellectual fluency, and ability to analyze and connect). 4) There are positive and statistically significant data between the behavior of the administrative leader who is interested in the staff and the level of their creativity. 5) There is no statistically significant data between the interest of the administrative leader in the work and the level of managerial creativity of the employees. 6) There are statistically significant relationships between personal and functional variables and some variables of leadership behavior, which are: (The presence of positive data statistically significant between the educational qualification, the functional rank of workers, and the level of managerial creativity, and the presence of negative data statistically significant between the functional rank of workers and the interest of the administrative leader to work). The study recommended the emphasis on the principle of delegation as a means and tool to develop the skills of creative staff by providing expertise and direct contact with situations and events, and support the concept of serious participation of workers in decision-making.